2005
DOI: 10.1007/bf03347566
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and tumor necrosis factor-α in gestational hyperglycemia

Abstract: The data support the developing hypothesis that low-grade systemic inflammation is associated to GDM, in particular for pregnant women without conventional risk factors for gestational hyperglycemia, whose insulin resistance seems less explainable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 36 publications
2
37
1
2
Order By: Relevance
“…These findings are in accordance with recent studies reporting that pregnancies with GDM are associated with low adiponectin levels during the 2 nd trimester [35][36][37] and increased levels of TNFα, IL-6 and high sensitivity (hs) CRP, all indicators of a pro-inflammatory status. 35,37,38 In the present study, it is shown that IL-1β levels follow a pattern similar to the other pro-inflammatory cytokines in pregnancies with GDM. The source of maternal pro-inflammatory cytokines during pregnancy is not entirely clear.…”
Section: Discussionsupporting
confidence: 72%
“…These findings are in accordance with recent studies reporting that pregnancies with GDM are associated with low adiponectin levels during the 2 nd trimester [35][36][37] and increased levels of TNFα, IL-6 and high sensitivity (hs) CRP, all indicators of a pro-inflammatory status. 35,37,38 In the present study, it is shown that IL-1β levels follow a pattern similar to the other pro-inflammatory cytokines in pregnancies with GDM. The source of maternal pro-inflammatory cytokines during pregnancy is not entirely clear.…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, a diet high in AGEs was found to promote inflammatory mediators that might be important in the genesis of diabetes, such as TNF-a and C-reactive protein [43]. Both biomarkers have been positively associated with the risk of GDM or gestational hyperglycaemia [44,45]. In addition, it has been proposed that food-derived AGEs may interact with glycoxidation-related genes, in particular, the AGE receptor (AGER) gene, to determine risk of type 2 diabetes by activating the AGE receptor signal transduction pathway involved in the inflammatory response [46].…”
Section: Discussionmentioning
confidence: 99%
“…Gestational diabetes mellitus is defined as glucose intolerance with onset or first recognition during pregnancy [1]. Women with gestational diabetes show various features of the metabolic syndrome [2] like obesity, low-grade inflammation [3] or hypertriacylglycerolaemia [4,5], and have an increased risk of developing type 2 diabetes mellitus [6]. Insulin resistance plays a major role in the adverse cardiovascular risk profile found in women with gestational diabetes.…”
Section: Introductionmentioning
confidence: 99%